1999
DOI: 10.1094/pdis.1999.83.11.1072a
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Hop Powdery Mildew in the Pacific Northwest

Abstract: Hop powdery mildew (HPM) was first observed in commercial hop (Humulus lupulus L.) fields in Washington State on 10 June 1997 near Toppenish in the Yakima Valley. The disease appeared throughout the valley in 1997; by mid-July, scattered fields throughout the Yakima growing area reported HPM. Approximately 2,000 of 30,000 acres in production were not harvested in 1997 due to HPM. The pathogen apparently perennated in buds, and flagshoots originating from infected buds were observed during March and April 1998 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…R6-based resistance provided a level of disease suppression that was equivalent to immunity to powdery mildew in the Pacific Northwest for 14 years. This was a crucial component of disease management programs developed following the destructive epidemics that followed the introduction of P. macularis to the Pacific Northwest in the mid 1990s (Ocamb et al 1999). This research demonstrates that isolates of P. macularis capable of overcoming R6 resistance are now widespread in the region and outbreaks of powdery mildew occur annually on formerly resistant cultivars.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…R6-based resistance provided a level of disease suppression that was equivalent to immunity to powdery mildew in the Pacific Northwest for 14 years. This was a crucial component of disease management programs developed following the destructive epidemics that followed the introduction of P. macularis to the Pacific Northwest in the mid 1990s (Ocamb et al 1999). This research demonstrates that isolates of P. macularis capable of overcoming R6 resistance are now widespread in the region and outbreaks of powdery mildew occur annually on formerly resistant cultivars.…”
Section: Discussionmentioning
confidence: 86%
“…Breeding for host resistance to powdery mildew on hop, caused by Podosphaera macularis, began in the early 1900s and continues to be a primary breeding focus in many breeding programs worldwide (Neve 1991;Salmon 1917). This is especially true for the U.S. Pacific Northwest (Washington, Oregon, and Idaho), where the disease became a major constraining factor for hop production after the introduction of the pathogen to the region in 1996 (Ocamb et al 1999). To date, seven R genes have been recognized in hop (named RB, R1, R2, R3, R4, R5, and R6) that can impart immunity to select isolates of P. macularis (Neve 1991;Seigner et al 2001).…”
mentioning
confidence: 99%
“…A recent outbreak of powdery mildew affecting Cascade in the U.S. Pacific Northwest (PNW) was the result of a Cascade-adapted isolate of P. Macularis [18]. Very little management was required to grow Cascade until powdery mildew was introduced in the PNW in the mid-1990s [28], and the rise of PM infection corresponds to an increase in Cascade acreage [18]. Hop breeding with resistant cultivars [26, 27, 29] can result in new resistance, but given the inevitability of pathogen adaptation, an understanding of the genomic features underlying resistance and susceptibility is necessary to breed for hop that can withstand pathogen adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Podosphaera macularis, the causal organism of powdery mildew on hop, the ascigerious stage is known to exist in Europe (Neve, 1991) and eastern North America (Blodgett, 1913), but has not yet been reported in the Pacific Northwest (Gent et al, 2006). Despite the hop industry being present in the Pacific Northwestern region of North America since the early 1900s (Neve, 1991;Barth et al, 1994), powdery mildew was not reported in hop yards of the Pacific Northwest until 1997 (Ocamb et al, 1999).…”
Section: Introductionmentioning
confidence: 99%